Journal "Topics in Early Childhood Special Education": assessment of the periodical and articles - Paulo Celso Pereira; Karyne de Souza Augusto Rios (Universidade Federal de Santa Maria (UFSM), 2008)
Journals have the purpose of dissemination and communication of scientific knowledge. As a vehicle to the dissemination of scientific productions, it is necessary the periodical assessment to evaluate the quality of research: accuracy, reliability and seriousness. The objective of this study is to assess the journal Topics in Early Childhood Special Education, considering for the analysis the whole journal and the formal and the contents aspects of all articles. The analysis revealed that the periodical satisfactorily fulfills the normalization criterion, the authors' instruction criterion and the articles assessment criterion. However, it was identified the need for major accuracy in the bibliographic legend that should appear on all pages of articles. Regarding the analysis of the articles it was observed the lack of keywords and a wide variety of information in the abstracts, which they were sometimes not related to the key aspects of the research. All authors and institutions are from United States of America and the type of study most published it was the research report. The participants' characterization indicated that the journal broachs different types of special needs, but there is more studies about autism. The study data confirm the journal purpose that is providing relevant and current information on all aspects of early education for children with special needs, including their families. It was pointed the need for more articles from other countries beyond the North American continent, including the participation of researcher from other countries. Additionally, the model used for the journal assessment showed to be effective in providing data quality, reliability and accuracy of the whole periodical and the studies that it was published in the journal.